2001
DOI: 10.1597/1545-1569_2001_038_0030_clapci_2.0.co_2
|View full text |Cite
|
Sign up to set email alerts
|

Cleft Lip and Palate Care in the United Kingdom—The Clinical Standards Advisory Group (CSAG) Study. Part 3: Speech Outcomes

Abstract: Objective To summarize speech outcomes in children born with unilateral cleft lip and palate (UCLP) throughout the United Kingdom. Design Prospective descriptive study on a cross-sectional sample of children. Patients/Participants Data were collected for 238 5-year-olds (born between April 1, 1989, and March 31, 1991) and 218 12-year-olds (born between April 1, 1982, and March 31, 1984) with complete UCLP. Main Outcomes Ratings of intelligibility, nasality, “speech cleft type characteristics” and speech therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
96
1
9

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(116 citation statements)
references
References 22 publications
10
96
1
9
Order By: Relevance
“…Our results compare favourably with outcome of other cleft centres . The audit of the quality of care for children with CUCLP in the UK showed that the mean prevalence of hypernasality was 29% of the 5‐year‐olds and 32% of the 12‐year‐olds. The findings of the ‘Dutchcleft’ study – a three‐centre randomised clinical‐controlled trial into the effects of infant orthopaedics on craniofacial growth and speech development – demonstrated that hypernasality was present in more than 30% toddlers .…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Our results compare favourably with outcome of other cleft centres . The audit of the quality of care for children with CUCLP in the UK showed that the mean prevalence of hypernasality was 29% of the 5‐year‐olds and 32% of the 12‐year‐olds. The findings of the ‘Dutchcleft’ study – a three‐centre randomised clinical‐controlled trial into the effects of infant orthopaedics on craniofacial growth and speech development – demonstrated that hypernasality was present in more than 30% toddlers .…”
Section: Discussionsupporting
confidence: 66%
“…The current findings demonstrate that speech development in children with CUCLP treated with the one‐stage surgical protocol was satisfactory. The prevalence of hypernasality – an important outcome measure – was low in the whole cohort irrespective of the method of the hard palate repair. Our results compare favourably with outcome of other cleft centres .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…These clinical measures have therefore been modified as the service has evolved. For speech, a validated measure has been developed , in contrast to the modified CAPS and a modification of the Eurocleft Speech study for articulation in CSAG . Differences between the two approaches are detailed in the speech study.…”
Section: Discussionmentioning
confidence: 99%
“…18% of 5-and 12-year-olds had consistent hypernasality of mild, moderate, or severe degree. Approximately two-thirds of both age groups had undergone speech therapy [88]. In India where unoperated adult cleft lip and palate is a significant problem, very few achieved normal speech [86], and communication is hampered by hearing problems with 76% of unoperated cleft palate patients showing mild to moderate conductive deafness [89].…”
Section: Quantifying the Morbidity Due To Ofcmentioning
confidence: 99%